Tax Policy to Accelerate EV Infrastructure and Reducing National Carbon towards Net Zero Emission - Mohamat Emir Ferdian (International Journal Labs, 2023)
More advanced technology in its development certainly leads to environmental issues in order to have an impact on a better environment and prevent global warming in the future. One of the technologies used is the shift of the use of fuel-based vehicles to battery-based electric vehicles. In its application and towards Indonesia Net Zero Emission in 2060, several challenges in the development of the Electric Vehicle ecosystem are still occurring, trying to look at other countries that have used electric vehicles more advanced, policies are very important in the success of the technological transition to environmentally friendly technology and prevent Global Warming. From a Tax Revenue sectors, Government could managed to increased or adjust the Carbon Tax for Industry which considered to be still very insufficient compared to other countries.